Essays on private capital flows and real sector growth in Africa - Asamoah, Michael Effah (My University, 2021)
Globally, countries continue to implement policies aimed at the attraction and retention of capital flows due to its perceived significant effect on economic growth and development. The benefits of capital flows are touted as being able to drive down domestic interest rates, smooth consumption, transfer of technology and improve the functioning of the financial sector. In as much as there is a copious body of literature on capital flows and economic growth, there remain essential areas that the literature has been silent. Among these are capital flows and real sector growth in the light of the allocation puzzle; the real sector amid financial sector development and institutions; private capital flows-macroeconomic volatility-financial development connections, and thresholds in the capital flows-real sector growth dynamics. Filling these gaps will provide the needed knowledge and policy directions on how countries that are known to depend on capital flows can harness these flows for growth and development, especially at the level of the real sector. Using robust econometric procedures, this study examined four thematic areas of capital flows in Africa. The first essay investigated the evidence and/or otherwise of an allocation puzzle and bi-directional relationship between private capital flows and real sector growth. The study covered 42 Sub-Saharan African (SSA) countries between 1980 and 2017. We used growth in manufacturing, industry, agriculture, and services to capture the real sector and proxied private capital flows by foreign direct investment, portfolio equity flows, and private non-guaranteed debt. We employed the two-step dynamic systems GMM model to establish our empirical relationships. We found no evidence in support of the allocation puzzle, which suggests that SSA countries with relatively high growth in the real sector will attract more private capital. However, at a decomposed level, we established a bi-directional relationship of a positive association between debt flows and growth in agriculture and services, with no evidence of an allocation puzzle. Though we found a bi-directional association between debt and industrial growth, the association was detrimental in both directions. Also, the study established a two-way inverse reverse effect between equity flows and manufacturing growth. Finally, while the impact of foreign direct investment on the real sector is positive at the disaggregated level, there is a positive bi-directional effect between foreign direct investment and growths in manufacturing, industry, and service value additions. The study provides a strong foundation for an alternative source of financing, especially for the growth of the service and agriculture sectors regarding debt and equity, from the reliance on the traditional FDI. The findings also indicate parallel reactions between real sector growth and private capital in SSA. The second essay had two separate objectives fused into one. The first part examined the brinks of financial development at which private capital to Africa enhances growth at the level of the real sector. We deployed a newly developed financial development dataset to moderate the association between private capital and the real sector, and the Lewbel instrumental variable two-step GMM estimator (IV –GMM), with Kleibergen-Paap robust standard errors and orthogonal statistics in establishing our empirical relationships over the period 1990 to 2017, for a sample of thirty (30) countries in Africa. Initial estimations at the overall level of the real sector, manufacturing, and industry show that FDI has no growth effects and even worsens the growth of the agriculture sector. Financial development stifles growth. On decomposing the real sector, we found the interaction between FDI and financial development to enhance the growth of the real sector and its components at face value. However, our marginal effect analysis shows that the growth impact of FDI on the overall real sector, industry, and service sector growth starts at the threshold level of the 25th percentile of financial development, while the growth impact on manufacturing is only evident at the 90thpercentile of financial development. Finally, although financial sector growth aids foreign direct investment in enhancing the growth of the agriculture sector, it cannot wholly eradicate the initial adverse impact from FDI. We further found that portfolio equity has no growth impact on Africa’s real sector, while debt flows harm the overall real sector, manufacturing, and industrial growth, but no impact on agriculture and services’ growth. We found that financial development reinforces the conservative view that capital flows enhance economic growth, but the reinforcement depends on the type of sector, either debt or equity, and the percentile levels of financial development. A similar objective was to analyze the interconnections between private capital flows, the quality of institutions, and the growth of the real sector in Africa. The study covers thirty (30) African countries. Our empirical analysis, with a panel data between 1990 and 2017, indicates that private capital flows (FDI, private debt, and equity) have no direct impact on the growth of the real sector. A decomposition divulges that FDI has no impact on manufacturing and detrimental to industrial and agriculture sectors. Portfolio equity is injurious to growth in services and unresponsive to the growth of all other sectors. Private debt was also insensitive to the growth in agriculture and services, and even damaging to manufacturing and industrial growth. Initial assessments show that countries with robust institutional frameworks can benefit significantly from capital flows, as we found institutions do moderate the positive impact of capital flows on the growth of the real sector, starting from the 25th percentile of institutions. Our marginal analysis confirms that the impact of private capital on real sector components is dependent on the type of capital, the sector, and the percentile level on institutions, in some cases, as far as the 90th percentile. Our results show that for policy implementation, it is not a case of one cup fits all, but sector-specific capital flow institutional policies should be the way forward. The orthodox view is that uncertainty is a deterrent to investment, and by extension, private capital inflows. Paying specific attention to the volatility of the domestic exchange rate, private capital flows and a newly developed indicator of financial development, the third chapter of the thesis examined the impact of exchange rate uncertainty on private capital flows, and whether financial development matters in such association. Specifically, the study sought to answer four questions: Is the exchange rate uncertainty –capital flows nexus strictly monotonic? Does exchange rate volatility deter capital flows? Can financial development mitigate the adverse effect of economic uncertainty on capital flows? At what threshold point does financial development jettison the negative impact? The study covers 40 countries over the period 1990 –2017. We establish our empirical relation with a system general method of moments (GMM) two-step robust estimator with orthogonal deviations. We found evidence in support of anon-linear U-shaped relationship between uncertainty and capital flows, and that the impact of uncertainty on capital flows depends on varying levels of uncertainty. We also document that uncertainty deters all forms of capital flows, and that countries with a well-functioning financial system can transform the adverse impact of volatility on capital flows. However, our marginal analysis shows that curbing the adverse effect of volatility on private capital depends on the type of capital flow, the indicator as well as the percentile level on financial sector development, in some cases as far as to the highest percentile. We further established that with the current state of the financial sector, financial institutions’ development offers the quickest route to curtailing the adverse impact of volatility on capital flows, as it has a lower threshold value or critical point compared with financial markets’ development. In the final essay, we investigated the possibilities of non-monotonic or nonlinearities in the capital flows - economic growth dynamics, as some studies posit that the effect of capital flows on economic growth changes course after attaining a certain threshold level, either based on the levels of capital flow itself or some mediating variables. We proxied capital flows by foreign direct investment (FDI) inflows and growth by real sector components. With data from 1990 to 2018, for a sample 36 African countries, the study employed Seo and Shin (2016) dynamic panels threshold effect with endogeneity as well as Seo et al. (2019) estimation of dynamic panel threshold model using Stata to achieve the study’s objectives. In the first part of the analysis, we employed three indicators of human capital development as threshold variables, and FDI flows as the regime dependent variables. These are the mean years of schooling, gross national secondary school enrolment, and primary school pupil to teacher ratio. In the subsequent analysis, we deployed FDI as both the threshold and regime dependent variable. The study found significant thresholds in the capital flows -real sector growth relationship as mediated by human capital and foreign direct investment. The significance impact of foreign direct impact on real sector happens at both the lower and upper levels of the mediating variable but the component of real sector matters. We established that in most cases, the impact of FDI on the growth of the real sector is harmful in the lower regime and beneficial in the upper regime of human capital for both manufacturing and services sectors, and vice versa for both agriculture and industrial sectors. The results indicate that increasing levels of human capital development and FDI inflows are necessary for the growth impact of FDI on Africa’s real sector, but not under all sectors as he results are dependent on the varying threshold variables of both human capital and foreign direct investment
A thesis submitted to the Faculty of Commerce, Law and Management of the University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance and Economics, 2021
Keywords: Real sector; Allocation puzzle; Financial developmet; Institutional quality; Volatility; Exchange rate; Thresholds; System GMM; Africa; UCTD; SDG-8: Decent work and economic growth